The association of psychological distress and burnout on job satisfaction among medical healthcare providers in the healthcare industry during the pandemic COVID-19 in Malaysia - Visshan, Miyanathan; Loochana, Krishna Rao; Adrianna, Silvarajah (2022)

(untitled)
This research paper aims to determine the association of job satisfaction with psychological distress and burnout among medical healthcare providers in the healthcare industry during the Pandemic COVID-19 in Malaysia. A cross-sectional quantitative study was performed on 95 Medical Healthcare Providers who worked during the Covid-19 Pandemic in Malaysia such as doctors, nurses, medical assistants, pharmacists, lab technicians and others. The participants were recruited using the selective sampling method. Statistical Packages for Social Science (SPSS) was used to run the analysis. The Spearman correlation coefficient was measured for the association between the variables and to test the underlying mechanism that could impact possible causal relationships. The results indicated a weak negative correlation between psychological distress and job satisfaction as well as a moderate negative correlation between burnout and job satisfaction among medical healthcare personnel during the Covid-19 Pandemic in Malaysia. The findings obtained from this study can be utilized to raise awareness as a potential strategy in boosting the mental health of healthcare providers by lowering stress and burnout in the future. This study can contribute to the development of similar studies by future researchers in Malaysia.